Determinants of Generation Z Interest in Using Bank Jago Syariah: Financial Literacy, Brand Trust, and Price Saving Orientation - Alifatul Afwah; Arif Afendi; Mardhiyaturrositaningsih Mardhiyaturrositaningsih; Muhammad Rasyidin (AL-ARBAH: Journal of Islamic Finance and Banking, 2026)
Purpose - This study aims to examine the effect of financial literacy, brand trust, and price-saving orientation on Generation Z’s intention to use Bank Jago Syariah in Semarang City. Method - The research method used in this study was quantitative. Data were collected through questionnaires distributed to 100 Generation Z respondents in Semarang using purposive sampling. The data were analyzed using multiple linear regression with SPSS version 26. Result - The results indicate that financial literacy, brand trust, and price-saving orientation have a positive and significant effect on Generation Z’s intention to use Bank Jago Syariah. Implication - These findings suggest that digital Islamic banks need to enhance financial education, strengthen brand credibility, and provide competitive financial benefits to attract younger users. Originality - This study contributes to the literature by examining the combined role of financial literacy, brand trust, and price-saving orientation in influencing Generation Z’s intention to use Islamic digital banking services. Keywords: Financial Literacy, Brand Trust, Price-Saving Orientation, Intention to Use, Generation Z